Dimensions of Compulsive Exercise across Eating Disorder Diagnostic Subtypes and the Validation of the Spanish Version of the Compulsive Exercise Test - Sauchelli, Sarah; Arcelus, Jon; Granero, Roser; Jiménez-Murcia, Susana; Agüera, Zaida; Del Pino-Gutiérrez, Amparo; Fernández-Aranda, Fernando (Frontiers in Psychology, 2016)
Objectives: Compulsive exercise in eating disorders has been traditionally considered as a behavior that serves the purpose of weight/shape control. More recently, it has been postulated that there may be other factors that drive the compulsive need to exercise. This has led to the development of the Compulsive Exercise Test (CET); a self-reported questionnaire that aims to explore the cognitive-behavioral underpinnings of compulsive exercise from a multi-faceted perspective. The objectives of this study were threefold: 1) To validate the Spanish version of the CET; 2) To compare eating disorder diagnostic subtypes and a healthy control group in terms of the factors that drive compulsive exercise as defined by the CET; 3) To explore how the dimensions evaluated in the CET are associated with eating disorder symptoms and general psychopathology. Methods: The CET was administered to a total of 157 patients with an eating disorder (40 anorexia nervosa, 56 bulimia nervosa, 61 eating disorder not-otherwise-specified (EDNOS)) and 128 healthy weight/eating controls. Patients were assessed via a semi-structured interview to reach a DSM-IV-TR diagnosis. Additionally, all participants completed the Symptom Checklist-90-Revised (SCL-90R) and the Eating Disorders Inventory-2 (EDI-2). Results: Confirmatory factor analysis demonstrated adequate goodness-of-fit to the original five-factor model of the CET. Bulimia nervosa and EDNOS patients scored higher in the avoidance and rule-driven behavior, weight control and total CET scales in comparison to the healthy controls, and higher across all scales apart from the exercise rigidity scale compared to the anorexia nervosa patients. Mean scores of the anorexia nervosa patients did not differ to those of the control participants, except for the mood improvement scale where the anorexia nervosa patients obtained a lower mean score. Mean scores between the bulimia nervosa and EDNOS patients were equivalent. The CET scales avoidance and rule-driven behavior, weight of control and total CET scores were positively correlated with the clinical assessment measures of the SCL-90R and EDI-2. Conclusion: Compulsive exercise is a multidimensional construct and the factors driving compulsive exercise differ according to the eating disorder diagnostic subtype. This should be taken into account when addressing compulsive exercise during the treatment of eating disorders.